2021
DOI: 10.1016/j.jsurg.2020.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Urology Residency Training With Real-World Workforce Needs

Abstract: Objective Research suggests recently graduated urology residents do not feel ready for independent practice. We conducted a study to determine if Accreditation Council for Graduate Medical Education (ACGME) minimum case requirements, resident case logs, and graduating resident perceived readiness for practice are aligned with the procedural demand and needs of the current urology workforce. Design Correlative study comparing the association between (1) workforce demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…A study from Germany showed that most (70%) urology residents are interested in learning urogynecology, but only half claim to receive proper training in their residency 15 . In a survey with chief residents and recently graduated urologists in the United States, most participants reported deficient subspecialty exposure 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study from Germany showed that most (70%) urology residents are interested in learning urogynecology, but only half claim to receive proper training in their residency 15 . In a survey with chief residents and recently graduated urologists in the United States, most participants reported deficient subspecialty exposure 9 …”
Section: Discussionmentioning
confidence: 99%
“…As a result, residents graduating from urology training programs throughout the world typically lack the skills to practice many urological subspecialties. In a survey that evaluated chief residents and recently graduated urologists regarding their residency program in the United States, most participants reported deficient availability of advanced skills for robotic and laparoscopic surgery and subspecialty exposure 9 . Most residents felt comfortable performing essential urological procedures such as cystoscopy, ureteroscopy, and open nephrectomy but expressed a lack of confidence in performing unsupervised advanced minimally invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a correlative study, Cruz et al demonstrated that ACGME minimum case log volumes do not guarantee surgical competency in independent surgical practice after training and may not reflect current urologic procedural demand. 3 We are all striving to slowly recover from the profound effects of COVID and seek a return to normalcy, both in the world in general and specifically in this study, for urologic residency training. For those of us involved with graduate medical surgical training programs, we will need to carefully assess and balance not only volume-based case log requirements but also competency-based requirements, in order to ideally prepare graduates for eventual independent practice in the future.…”
mentioning
confidence: 96%